METHODOLOGICAL FOUNDATIONS FOR DEVELOPING PROFESSIONAL COMPETENCE IN CADETS OF HIGHER MILITARY EDUCATIONAL INSTITUTIONS - Yuldashev Askar Khudoyberdiyevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article discusses the methodological foundations for developing professional competence in cadets of higher military educational institutions.